Nanostructured poly(aniline-co-metanilic acid) as platinum catalyst support for electro-oxidation of methanol. (19th February 2015) - Wu, Tzi-Yi; Chen, Bor-Kuan; Chang, Jeng-Kuei; Chen, Pin-Rong; Kuo, Chung-Wen
Abstract Nanostructured poly(aniline-co-metanilic acid) is prepared using the chemical oxidative polymerization of aniline (Ani) and metanilic acid (Maa). The copolymerization of poly(aniline-co-metanilic acid) with various molar feed ratios of Ani/Maa is conducted to attain highly porous nanowire copolyanilines. The as-prepared copolyanilines are characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). The XPS results indicate that a saturated doping state is achieved when the Ani/Maa ratio is less than 20/1. The SEM images reveal that these films are composed of highly porous nanowires when the feed molar ratio of Ani/Maa is more than 4/1. The copolyanilines are used as Pt catalyst supports. Transmission electron microscopy (TEM) results indicate that Pt particles disperse more uniformly onto the highly porous nanowires of P(A10-M) (feed molar ratio = 10:1) than onto other copolyanilines, and that the P(A10-M)-Pt electrode has the highest active surface area. Cyclic voltammetry results and chronoamperometric response measurements show that the P(A10-M)-Pt electrode has the highest electrocatalytic activity and the best long-time stability toward methanol oxidation among polyaniline-Pt and copolyaniline-Pt electrodes.